STRATEGI MARKETING POLITIK DINI INAYATI DALAM PENCALONAN ANGGOTA LEGISLATIF PEMILIHAN UMUM 2024 - Novayana Damanik; Siti Muslikhatul Ummah (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study analyzes the political marketing strategy of Dini Inayati in the 2024 Legislative Election in Semarang City Electoral District III, covering Tembalang and Candisari Districts. This research uses a qualitative descriptive approach with interviews and documentation as data collection techniques. The analysis framework applied is the Segmentation, Targeting, and Positioning (STP) approach proposed by Firmanzah (2008). The results indicate that Dini Inayati implemented a structured and systematic political marketing strategy. In terms of segmentation, she focused on women voters, particularly housewives, productive-age women, and women active in religious communities such as Islamic study groups. In terms of targeting, she directed her campaign program specifically toward women through empowerment initiatives, including support for women's micro and small enterprises, social community activities, and education on women's participation in public and political life. In terms of positioning, Dini Inayati built her political image through the identity of a "mother of three children" who remains active in social and political activities, creating emotional closeness with women voters. The three STP elements were implemented in an integrated and consistent manner, forming a coherent political marketing strategy that contributed to her success in winning a seat in the Semarang City Regional Legislative Council for the 2024–2029 period.